Persistent Infection Caused by Hobi-Like Pestivirus - Decaro, Nicola (American Society for Microbiology, 2013)
A calf persistently infected by Hobi-like pestivirus was monitored for about 6 months, displaying clinical signs typical of bovine viral diarrhea virus persistent infection and shedding the virus through all body secretions, with maximal titers detected in urine. This report provides new insights into the pathogenesis of the emerging pestivirus.